Effective communication the helping interview - Walter, Thomas; Dignam, Janet; Concept Media (New York, NY : Insight Media, 2004)
Illustrates effective communication techniques necessary for nursing professionals. This part 2, presents techniques for handling both the client-initiated interview and the professional-initiated interview, as well as opening, questioning and the use of silence
part 2. Opening, questioning and use of silence
Title from title screen
Keywords: Nurse and patient; Communication in nursing; Interpersonal communication; Interviewing